Activation of the cisplatin and transplatin complexes in solution with constant pH and concentration of chloride anions; quantum chemical study - Zimmermann, Tomáš; Leszczynski, Jerzy; Burda, Jaroslav V (Journal of molecular modeling, 2011)
The thermodynamics of cisplatin and transplatin hydration is studied within the model of constant pH solution. Several implicit solvation models were chosen for the determination of pK(a) and pK constants of the hydration reactions. The polarizable dielectric model (DPCM), integral equation formalism polarizable model (IEFPCM), and polarizable conductor model (CPCM) were combined with the 'united atom model for Hartree-Fock' (UAHF) method for cavity construction and the B3LYP/6-31++G(2dp,2pd) level of calculations for the determination of electronic energies. The results were compared with the COSMO-RS and SM8 model developed by Truhlar (with M06 and MPWX functionals and the charge model CM4). The RMS difference between experimental and calculated pK(a) values of cis/transplatin, water, HCl, and NH (4) (+) was used to evaluate accuracy of calculations. The DPCM model was confirmed to perform the best. The predicted pK(a) constants were used in Legendre transformation for the estimation of the ΔG' energies in the constant-pH model. The dependence of the pK constant on pH is plotted and compared with experimental value at pH=7.4. The influence of various chloride concentrations on the molar fractions of dissolved forms of cisplatin is examined for the DPCM model. The increased ratio of cisplatin active aqua-forms is clearly visible for 4 mM chloride solution in comparison with 104 mM Cl(-) concentration.
Keywords: Chlorides; Algorithms; termodynamika; hydrolýza; chemické modely; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Computer Simulation; Quantum Theory; cisplatina; Models, Chemical; Thermodynamics; algoritmy; komplexní sloučeniny; kvantová teorie; Hydrolysis; počítačová simulace; Coordination Complexes; chloridy; Cisplatin